1971
DOI: 10.1037/h0031082
|View full text |Cite
|
Sign up to set email alerts
|

Aggression as a function of expected retaliation and aggression level of target and aggressor.

Abstract: The effects of previous aggression level of aggressor and target persons, along with level of threatened retaliation, were investigated in an experimental situation which required aggressive responding. Males selected from 10 third-grade classrooms, four aggressors and two targets from each class, were classified as high or low in aggressiveness. Each aggressor responded to a high and low aggressive target; half of the aggressors expected retaliation and half did not. The results suggest that low aggressive bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…It is probably fairly common in Finnish education to encourage defence against one's equals whereas offensive aggression is not approved of. The results were partly in accordance with Peterson's (1970) findings: aggressive reactions are more intense the higher the risk of retaliation. The risk of retaliation is higher when the target is a boy of the same size than if he is a weaker peer.…”
Section: Discrimination Between the Targets Of Aggressionsupporting
confidence: 88%
“…It is probably fairly common in Finnish education to encourage defence against one's equals whereas offensive aggression is not approved of. The results were partly in accordance with Peterson's (1970) findings: aggressive reactions are more intense the higher the risk of retaliation. The risk of retaliation is higher when the target is a boy of the same size than if he is a weaker peer.…”
Section: Discrimination Between the Targets Of Aggressionsupporting
confidence: 88%
“…This implies that personality variables might interact with situational variables to produce different perception and reactions to aggression. This conclusion is supported to some degree by Paterson's (1970) study. Paterson found that highly aggressive children responded more aggressively when there was a threat for retaliation than when there was no such threat.…”
Section: Introductionsupporting
confidence: 65%
“…Thus, it would be expected that children could provide valid ratings of aggression in their peers, regardless of age. Indeed, several studies have indicated that third to sixth graders' peer ratings of aggression accurately predict observed levels of aggressive behavior (Peterson, 1971; Winder & Wiggins, 1964; Williams, Meyer, Eron, & Semler, 1967). The findings of the present series of studies suggest that such accuracy may extend downward as far as the first grade.…”
Section: Discussionmentioning
confidence: 99%